Is Nox4 a key regulator of the activated state of fibroblasts in systemic sclerosis?. Issue 9 (September 2014) - Böhm, Markus; Dosoki, Heba; Kerkhoff, Claus
Abstract The family of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases consists of phagocytic gp91phox and six‐related isoforms. Recent evidence indicates that the NADPH oxidase isoform Nox4 controls vascular, renal and pulmonary injury. We propose that Nox4 is an intrinsic regulator of the activated state of dermal fibroblasts in systemic sclerosis (SSc). Profibrotic cytokines on the one hand and antifibrogenic factors such as α‐melanocyte‐stimulating hormone on the other hand may target Nox4 as an intracellular nodal point. Via increased or decreased generation of reactive oxygen species and/or hydrogen peroxide, Nox4 could orchestrate collagen synthesis, differentiation of dermal fibroblasts into a profibrotic myofibroblast phenotype and thus dermal fibrosis. Confirmation of this hypothesis will have important consequences in our understanding of the activated state of dermal fibroblasts in SSc. Based on the availability of clinically useful Nox4 inhibitors, novel antifibrotic therapies of SSc can be envisioned.